2008
DOI: 10.1038/npp.2008.58
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors Regulate Nicotine-Enhanced Brain Reward Function and Intravenous Nicotine Self-Administration: Role of the Ventral Tegmental Area and Central Nucleus of the Amygdala

Abstract: Nicotine is considered an important component of tobacco responsible for the smoking habit in humans. Nicotine increases glutamatemediated transmission throughout brain reward circuitries. This action of nicotine could potentially contribute to its intrinsic rewarding and reward-enhancing properties, which motivate consumption of the drug. Here we show that the competitive N-methyl-D-aspartate (NMDA) receptor antagonist LY235959 (0.5-2.5 mg per kg) abolished nicotine-enhanced brain reward function, reflected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
134
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 79 publications
9
134
2
Order By: Relevance
“…Therefore, blockade of nicotine-induced dopamine release in the NAcc shell may not be the only mechanism by which LY379268 increases the latency to self-administer nicotine and attenuates nicotine intake. As described in the Introduction, LY379268 decreases glutamate release by activating inhibitory presynaptic mGlu2/3 receptors (Cartmell and Schoepp, 2000;Xi et al, 2002a), and blockade of glutamatergic neurotransmission also attenuates the reinforcing effects of nicotine (Kenny et al, 2009(Kenny et al, , 2003Palmatier et al, 2008;Paterson and Markou, 2005;Paterson et al, 2003). Therefore, mGlu2/3-mediated attenuation of glutamatergic neurotransmission is likely to be another mechanism contributing to LY379268-induced increases in the latency to self-administer nicotine (this study) and attenuation of the reinforcing effects of nicotine .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, blockade of nicotine-induced dopamine release in the NAcc shell may not be the only mechanism by which LY379268 increases the latency to self-administer nicotine and attenuates nicotine intake. As described in the Introduction, LY379268 decreases glutamate release by activating inhibitory presynaptic mGlu2/3 receptors (Cartmell and Schoepp, 2000;Xi et al, 2002a), and blockade of glutamatergic neurotransmission also attenuates the reinforcing effects of nicotine (Kenny et al, 2009(Kenny et al, , 2003Palmatier et al, 2008;Paterson and Markou, 2005;Paterson et al, 2003). Therefore, mGlu2/3-mediated attenuation of glutamatergic neurotransmission is likely to be another mechanism contributing to LY379268-induced increases in the latency to self-administer nicotine (this study) and attenuation of the reinforcing effects of nicotine .…”
Section: Discussionmentioning
confidence: 94%
“…Nicotine increases glutamatergic transmission by activating excitatory nicotinic receptors located on presynaptic glutamatergic terminals (Fu et al, 2000;Mansvelder and McGehee, 2002;Reid et al, 2000). Blockade of glutamatergic neurotransmission by systemic administration of receptor antagonists that act at postsynaptically located ionotropic or metabotropic glutamate (mGlu) receptors attenuated both nicotine selfadministration (Kenny et al, 2009(Kenny et al, , 2003Palmatier et al, 2008;Paterson and Markou, 2005;Paterson et al, 2003) and nicotine-induced increases in NAcc dopamine release (Fu et al, 2000;Kosowski et al, 2004;Schilstrom et al, 1998;Sziraki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nicotine self-administration in rats upregulates the expression of NMDAR subunits in the VTA and amygdala (Kenny et al, 2009). In vivo blockade of the NMDAR by NMDAR antagonists diminishes nicotineinduced dopamine release (Schilstrom et al, 1998) and nicotine self-administration (Kenny et al, 2009), but promotes tolerance to nicotine administration in rats (Shoaib et al, 1994;Shoaib and Stolerman, 1992). NMDAR antagonism could therefore constitute a target in the treatment of nicotine dependence, although to date this has not been successful in humans (Liechti and Markou, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamate is the prime excitatory neurotransmitter in the central nervous system (CNS) and binds to several receptors, including the ionotropic N-methyl-D-aspartate receptor (NMDAR). Animal studies have reported that nicotine increases glutamate concentrations in the ventral tegmental area (VTA) (Fu et al, 2000;Schilstrom et al, 2000) and exerts an excitatory effect on the NMDAR in dopaminergic neurons in the VTA (Fu et al, 2000;Grillner and Svensson, 2000;Mansvelder and McGehee, 2000), the nucleus accumbens (Schilstrom et al, 1998), and the central nucleus of the amygdala (Kenny et al, 2009). In addition, nicotine self-administration in rats upregulates the expression of NMDAR subunits in the VTA and amygdala (Kenny et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation